Istaid Center Medan's Da'wah Strategy in Countering Extreme and Liberal Narratives in the Post-truth Era - Siregar, Rahmat Mubarok; Muin, Mohd Iqbal Abdul (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the Islamic Thought and Information for Da’wah (ISTAID) Center Medan's da'wah strategy in responding to and countering the growth of extreme and liberal religious narratives in the post-truth era. The study focuses on the da'wah strategy implemented, the challenges faced, and the impacts felt by the congregation and the institution. This study aims to understand how ISTAID designs and implements da'wah oriented towards fostering a holistic and responsible understanding of religion amidst the rapid flow of digital information. The research method used is a qualitative descriptive case study approach. Data were obtained through in-depth interviews with ISTAID administrators, religious teachers (ustadz) who provide lectures, and participants in youth development programs, supplemented by secondary data sourced from relevant journals and books. The results show that ISTAID develops a da'wah strategy through da'wah bulletins, weekly face-to-face lectures, and tiered cadre development. This strategy helps the congregation develop a critical attitude towards religious information and avoid narrow or too loose understanding. Furthermore, strengthening the community and cadres of Islamic preachers is a crucial factor in maintaining the sustainability of ISTAID's Islamic preaching in the post-truth era, which is rife with disinformation and fragmented religious discourse.